Handshake, No. 8 (January 2013) - International Finance Corporation (International Finance Corporation, Washington, DC, 2015)
This issue includes the following headings: infrastructure - A new direction for New Zealand schools, Primary schools, primary importance, Sustainable school buildings, and PPPs build the future; services - A charter for change, vouching for the future, Low fees, high hopes, Private schools for the poor, and Governments and business schools; innovation - Education for the 21st century, Access for all, Bricks and clicks, Open education goes the distance, Grading teachers, M is for mobile, Online learning; and interviews - Michelle Rhee, Emily Lawson, and Arne Duncan.